Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Konsumen Pada Bengkel Kabia Jaya Motor (KJM) Pondok Timur Indah Bekasi - Achmad Akbar, Anggi; Wahyu Setyawati, Novita; Dwikotjo Sri Sumantyo, Franciscus (Fibonacci: Jurnal Ilmu Ekonomi, Manajemen dan Keuangan, 2025)
Consumer satisfaction is the comparison between expectations before making a purchase and perceptions of performance after purchase. Consumers are not satisfied when performance falls short of expectations. Consumers will be satisfied if they get the expected performance. If performance exceeds expectations, consumers are even more pleased and satisfied. The purpose of this study was to determine the effect or relationship between the independent variables, namely service quality and trust, on the dependent variable, namely consumer satisfaction at the Kabia Jaya Motor (KJM) workshop in Pondok Timur Indah, Bekasi, either partially or simultaneously. Sampling was done using purposive sampling, using the Lameshow formula, and a sample of 100 respondents was obtained. The results showed that the service quality and trust variables have a positive and significant effect on customer satisfaction, either partially or simultaneously.